2018
DOI: 10.14236/jhi.v25i1.963
|View full text |Cite
|
Sign up to set email alerts
|

Completeness and accuracy of anthropometric measurements in electronic medical records for children attending primary care

Abstract: Background Electronic medical records (EMRs) from primary care may be a feasible source of height and weight data. However, the use of EMRs in research has been impeded by lack of standardisation of EMRs systems, data access and concerns about the quality of the data. Objectives The study objectives were to determine the data completeness and accuracy of child heights and weights collected in primary care EMRs, and to identify factors associated with these data quality attributes. Methods A cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…The NLME-A method detected duplications, decimal point and unit errors in all datasets but transpose and addition errors seemed to be unique to Dogslife and CLOSER data with simulated errors. The prevalence of errors in our datasets ranged from 0.25% to 3.31%, which is within the same range as previous studies that have identified implausible values in growth data [9][10][11][12][13]. The presence of duplications and errors in medical records emphasises the importance of cleaning datasets even if they have been recorded by professionals.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The NLME-A method detected duplications, decimal point and unit errors in all datasets but transpose and addition errors seemed to be unique to Dogslife and CLOSER data with simulated errors. The prevalence of errors in our datasets ranged from 0.25% to 3.31%, which is within the same range as previous studies that have identified implausible values in growth data [9][10][11][12][13]. The presence of duplications and errors in medical records emphasises the importance of cleaning datasets even if they have been recorded by professionals.…”
Section: Discussionsupporting
confidence: 82%
“…It is difficult to distinguish errors from genuine anomalies in certain types of data, such as height and weight records, because biological data is heterogenous and may contain unusual but plausible values. These datasets are variable in terms of how accurate they are, with authors estimating error rates to be anything from 0.03% to 4.5% [9][10][11][12][13]. Since the first computational cleaning method for longitudinal growth [14] there have been enormous technological advancements, yet there remains no standardised data cleaning method.…”
Section: Introductionmentioning
confidence: 99%
“…38 The completeness and accuracy of child height and weight measurements in EMRALD were examined previously and shown to be of high quality. 39 Another analysis of weight status that used EMRALD data highlighted the strengths and limitations of this data source: 40 a strength is the adequate sample size to investigate severe obesity prevalence, and a limitation is the lack of generalizability to all children in the Ontario and Canadian populations. Our EMRALD study population differed from the overall Ontario population on factors related to obesity 41 and to routine use of primary care such as age, immigration status and neighbourhood income.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…sets out to report completeness of data about obesity in childhood records. They found that over 90% of records had valid information about their Canadian network 8. My sense is that the completeness of data in computerised medical records is improving over time, and with obesity, such an international problem having data about complete cohorts is really valuable.…”
Section: Child Healthmentioning
confidence: 99%